Effects of Cleaning Interval, Hapa Layers and Stocking Density on Growth Performance of Sandfish Holothuria scabra Juveniles in Ocean‐Based Nursery Production Systems - Jonh Rey L. Gacura; Jay R C. Gorospe; Racelle R. Rescordado; Paul C. Southgate; Margarita de laTorre‐de la Cruz (Aquaculture, Fish and Fisheries)
ABSTRACT The mass production of release‐size H. scabra juveniles in the Philippines is primarily done in a floating hapa ocean‐based nursery systems. To optimize its production, understanding the influence of different culture conditions and their management is necessary. In this study, the effects of hapa net cleaning interval, hapa layers, and stocking density on growth and survival of sandfish juveniles reared in floating hapa (L × W × H: 1.7 m × 0.9 m × 1.2 m) nursery system were assessed in two 60‐day field studies. Results showed that the number of hapa net layers and cleaning interval had negligible effects on the growth performance of sandfish juveniles by day 30. However, sandfish juvenile survival was affected by hapa net layers with higher survival in triple‐layer mosquito net hapas (40.5 ± 0.97%) compared to double‐layer mosquito net hapas (17.8 ± 0.62%). By day 60, the growth performance of sandfish juveniles in double‐layer hapas was higher (average weight: 5.0 ± 0.97 g; AGR: 0.13 ± 0.03 g day−1) compared to that in triple‐layer mosquito hapa nets (average weight: 3.1 ± 0.23 g; AGR: 0.07 ± 0.01 g day−1). Survival of sandfish juveniles reared in double‐layer mosquito net hapas, cleaned at 5‐day intervals (85.9 ± 4.58%) was significantly lower compared to all other treatments. Conversely, initial juvenile stocking density did not significantly affect the growth performance and survival of sandfish juveniles in both rearing cycles. We therefore recommend the use of triple‐layer mosquito net hapas during the first 30‐day culture period and an initial stocking density of 1000 post‐settled sandfish juveniles to increase production output. After 30 days, when the juveniles are larger, the use of double‐layer mosquito net hapas and lower stocking density are recommended to reduce cost and enhance growth performance. Where cleaning is necessary, hapa nets may be cleaned at 10‐day intervals to improve survival. The results of this study have important implications for optimizing the production of release‐size sandfish in ocean‐based nursery systems in the Philippines.